Analysis and Design of Surgical Instrument Localization Algorithm - Lu, Siyu; Yang, Jun; Yang, Bo; Yin, Zhengtong; Liu, Mingzhe; Yin, Lirong; Zheng, Wenfeng (Computer modeling in engineering & sciences, 2023)
With the help of surgical navigation system, doctors can operate on patients more intuitively and accurately. The positioning accuracy and real-time performance of surgical instruments are very important to the whole system. In this paper, we analyze and design the detection algorithm of surgical instrument location mark, and estimate the posture of surgical instrument. In addition, we optimized the pose by remapping. Finally, the algorithm of location mark detection proposed in this paper and the posture analysis data of surgical instruments are verified and analyzed through experiments. The final result shows a high accuracy.